An Analysis of Flouting Maxim in Her Movie By Spike Jonze - Viryani , Ni Made Jesi; Putri , I Gusti ayu Vina Widiadnya; Marantika , I Made Yogi (Journal of Language and Applied Linguistics, 2023)
The aims of study is deals with the study of flouting maxim in a movie entitled Her. People in conversation can run smoothly if they follow the cooperative principle. Grice (1975)stated that a cooperative principle in which at the stage at when it occurs by receiving the purpose or direction exchange in which you are engaged. There are four maxims that make up the cooperative principle namely maxim of quality, maxim of quantity, maxim of relevance, maxim of manner. However, not all conversation runs smoothly, sometime people are uncooperative while conveying the information, this case known as flouting maxim. This study discusses maxim that flouted by the characters in the Her movie. This study focuses on analyzing the types of flouting maxim and the reason why the characters flouted the maxims in the Her movie. There are two theories used to analyze the data in this research. First, the theory of cooperative principle was proposed by Grice (1975) to analyze the type of floating maxim and the second theory from Leech (1983) to analyze the reason of the flouting maxim. The researcher used descriptive method qualitative method to describe the data to answer the problem of the study. The result of the study shows that there are 10 data of floating maxim in Her Movie.